Factors influencing the health status of young athletes (One Health & Risk Management, 2021)
Introduction. The conditions of the occupational and living environment, and behavioral factors have a special importance in maintaining and strengthening the health of athletes, as well as in obtaining sports performance.Material and methods. In order to highlight possible health risk factors, it was developed a questionnaire to study the social and hygienic aspects, the health status and nutritional behaviors of young athletes practicing football, basketball, volleyball, handball and tennis. The target group consisted of 173 athletes from Chisinau, aged between 15-18 y.o.Results. It was found that junior athletes feel stress with different frequency, namely: rarely in 32.0-66.7% of cases, occasionally in 13.3-60% of cases and quite often 4.5-30,3%. It was found that 6.9% of junior athletes report unsatisfactory training conditions. We also considered it important to evaluate the psychological climate during the training activities of junior athletes. An inappropriate psychological climate was reported by 11.0% of respondents. The highest rate of the very tense psychological climate was declared by footballers - 31.6%, followed by handball players - 11.1%. Less than half (45.7%) of the respondents were firm in their opinion that they eat healthy, showing a significant divergence depending on the chosen sport - from 23.3% among tennis players to 57.4% among football players. Every seventh respondent stated that they did not keep track of their diet - 14.5%, which further confirms the lower level of knowledge of health promotion and gaps in activities to promote a healthy lifestyle. On average per total sample size, 75.1% of respondents usually have breakfast, of which over 60% of people have 1-2 servings. More often, for breakfast, they serve porridge (47.8%), omelet or boiled eggs (38.4%), bread with butter and tea (60.8%). It was negatively estimated that 3.4% of respondents per total sample size, omit lunch, as a rule, and 7.5% of people who eat lunch (from 3.0% among those who play handball to 16.0% of among those who practice volleyball) do not serve first course. At the same time, on average 50.3% per total sample size, with fluctuations from 44.0% (volleyball) to 59.1% (football), serve the first course with a frequency of 2-3 times a week. Respondents' views on the consumption of nutritional supplements and biologically active substances differ from one sports type to another. It should be noted that the share of people who stated that they have knowledge about biologically active substances ranged from 13.3% in the group of young athletes, who play tennis and volleyball, to 33.3% in the group of football players, a fact estimated negatively from the point of view of public health, since uninformed people, as a rule, make a lot of mistakes, which have a negative impact on their health. The highest share of respondents who stated that they do not have knowledge in that field was registered in the group of footballers - 52.7%.Conclusions. The level of providing the body with various nutrients and energy among junior athletes, as a result of the consumption of the studied rations, is different depending on the sport practiced, and partly depending on their gender.The appropriate hygienic and training conditions, compliance with the requirements for a balanced nutrition, regular medical examinations, and prevention of injuries can help maintaining the health of junior athletes, thus ensuring its durability.
Keywords: young athletes; lifestyle; risk factors; prevention.